Does it matter who invests in your country? - Kalman Kalotay (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
Indirect FDI – investment in which immediate investors differ from ultimate owners – plays an increasingly important role in corporate strategies and financial management. This Perspective analyses its different forms, explores its implications for development and suggests ways to minimize the potential negative impact of such investment.
Keywords: 330